PENGARUH PERTUMBUHAN UMKM TERHADAP PENINGKATAN EKONOMI MASYARAKAT MELALUI PKK DI DESA TANJUNG AGUNG KECAMATAN LENGKITI - Malini, Hema; Candra, Evan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Finding out how MSME growth affects improving the community's economy through PKK in Tanjung Agung Village, Lengkiti District, was the aim of this study. The equation, Y = 3.967 + 0.789X, was derived from the results of the basic linear regression test. According to the correlation coefficient's R value, which was determined using the interpretation guideline table, R = 0.744 falls between 0.60 and 0.799, indicating a strong association between the MSME growth variable (X) and Community Economic Development (Y). The results of MSME Growth (X) and Community Economic Improvement (Y) are proven by partial tests or t-tests, namely producing a t-value for the MSME Growth variable (X) of 5.670 Because t-count > t-table, namely 5.670 > 2.056, Ho is rejected and Ha is accepted, indicating a significan relationship between MSME Growth (X) and t-table, which is 2.056 and Community Economic Improvement (Y) Through PKK in Tanjung Agung Village, Lengkiti District, even though the r square number (determination coefficient) is 0.553, or 55.3%..